Examining The Impact of Hustle Culture on South Korean Workers - Hasanah, Ummul; Vardhani, Nabilla Kusuma; Martha, Fajarasih Luthfia (East Asian Review, 2024)
In recent years, the term hustle culture has often been heard among young workers. Through a hustle culture, a company's progress, which ultimately affects a country's progress, will be possibly achieved more quickly. However, criticism has been common that hustle culture interferes with the mental health of workers in a company because they are too overworking. South Korea has long been known as a country with workers carrying out a hustle culture. This culture can be seen in some of the depictions of Korean popular culture, such as in the Korean drama "Good Manager." The purpose of this research was to find out and reveal the hustle culture and its effects, both for companies and employees in a company in the Korean drama "Good Manager." The analysis was carried out using a qualitative descriptive method from the data contained in the Korean drama "Good Manager." The data were collected through a literature study from various references and observations. The results of this study are expected to be useful for Indonesian youth who work in companies to imitate and implement the hustle culture if it is seen as good. Hopefully, with this research, Korean culture enthusiasts will be better prepared for the challenges they face when they work in companies that adhere to Korean work culture. In addition, the public can better understand the dangers of a hustle culture and be able to maintain mental health from an unhealthy work culture.